Digitalization, as focal tactical strategy, within collaborativelearning; case study: Mathematics - Williams Basantes-Valverde; Daysi Astudillo-Condo; Katherine Tixi-Gallegos (Educación y Sociedad)
Initially, it is necessary to infer the way in which teachers contribute knowledge to thesmart classroom. To this end, the objective of this study, as the basis of the educationalenvironment and within digital pedagogy, manifests the didactic ability as a technicality ofinstruction. However, this research is based on the prism methodology and the bibliographyadmits technology as a bastion of ubiquity in resulting edges. Thus, digital connection isconsidered as the driving force of learning and its competencies are focus strategies. As muchas these serve as educational tools in the digital age, they promote knowledge and expose,as derivation, cognitive thinking; safeguarding, in the classroom universe, competencies as astandard and establishing digitalization as the foundation of learning. Finally, in their search,technological instruments and computational certainty supported a practical assumption; caseof Mathematics in an Ecuadorian University.